Exercise delays aging: evidence from telomeres and telomerase —a systematic review and meta-analysis of randomized controlled trials - Sun, Liang; Zhang, Tingran; Luo, Lanfang; Yang, Yi; Wang, Chuanqiushui; Luo, Jiong (Frontiers in Physiology, 2025)
ObjectiveTo systematically evaluate the regulatory effects of exercise intervention on telomere length (TL) and telomerase activity (TA), and to provide evidence for formulating precise exercise prescriptions based on telomere protection.MethodsDatabases including China National Knowledge Infrastructure, Wanfang, VIP, PubMed, Web of Science, Cochrane Library, and Embase were searched to collect randomized controlled trials (RCTs) regarding the regulation of TL and TA by exercise intervention up to February 2025. The Cochrane risk assessment tool was used to evaluate the quality of the included literature. Meta-analysis, heterogeneity test, subgroup analysis, sensitivity analysis, univariate meta-regression analysis, and publication bias test were conducted using Review Manager 5.3 and Stata 18.0 software.ResultsExercise intervention significantly maintained TL (SMD = 0.59, 95% CI: 0.14–1.06, P = 0.01) and enhanced TA (SMD = 0.35, 95% CI: 0.20–0.51, P < 0.00001). A single study suggests high-intensity interval training (HIIT) may maintain TL (SMD = 0.66, P = 0.01), but this requires further validation due to limited evidence. Aerobic exercise (AE) consistently increased TA (SMD = 0.33, P = 0.0001), while resistance exercise (RE) showed non-significant trends (SMD = 0.16, P = 0.43). Subgroup analysis by sex showed a trend toward greater TL maintenance in females (SMD = 0.48, P = 0.06) compared to males (SMD = 0.38, P = 0.40). An exercise duration of ≥16 weeks was necessary for significant effects. High heterogeneity (I2 = 92% for TL) was partially explained by measurement methods, age, and baseline health.ConclusionExercise maintains TL and enhances TA, potentially contributing to delayed aging. AE shows robust effects on TA, while HIIT and RE require further research due to limited studies. Future studies should standardize measurement methods and explore confounders like diet and genetics.Systematic Review RegistrationPROSPERO, identifier CRD420251006569.